2017
DOI: 10.1093/infdis/jix046
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Activity of World Health Organization–Recommended Formulations Against Enveloped Viruses, Including Zika, Ebola, and Emerging Coronaviruses

Abstract: The World Health Organization (WHO) published 2 alcohol-based formulations to be used in healthcare settings and for outbreak-associated infections, but inactivation efficacies of these products have not been determined against (re-)emerging viruses. In this study, we evaluated the virucidal activity of these WHO products in a comparative analysis. Zika virus (ZIKV), Ebola virus (EBOV), severe acute respiratory syndrome coronavirus (SARS-CoV), and Middle East respiratory syndrome coronavirus (MERS-CoV) as (re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
158
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 12 publications
(17 reference statements)
7
158
0
2
Order By: Relevance
“…after removing gloves. Two WHO recommended formulations (based on 80% ethanol or 75% 2-propanol) have been evaluated in suspension tests against SARS-CoV and MERS-CoV, and both were described to be very effective [14]. No in vitro data were found on the efficacy of hand washing against coronavirus contaminations on hands.…”
Section: Discussionmentioning
confidence: 99%
“…after removing gloves. Two WHO recommended formulations (based on 80% ethanol or 75% 2-propanol) have been evaluated in suspension tests against SARS-CoV and MERS-CoV, and both were described to be very effective [14]. No in vitro data were found on the efficacy of hand washing against coronavirus contaminations on hands.…”
Section: Discussionmentioning
confidence: 99%
“…Another important consideration in selection of hand hygiene agents, particularly in resource-poor countries, is cost and availability. Alcohol-based hand rub formulations proposed by the WHO have recently been shown to be effective against enveloped viruses including emerging Zika, EBOV, SARS-CoV and MERS-CoV in vitro [51], and may be a more freely available and cost-effective alternative to medicated cleansers/antiseptics. Since hand rubs cannot properly cleanse soiled hands [2], a phased approach as recommended by the National Institute for Health and Care Excellence [52] may be an optimized approach to handle situations where increased hand hygiene is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol (60%-85%) appears to be the most effective against viruses compared to isopropanol (60%-80%) and n-propanol (60%-80%) [23]. The study conducted with WHO-recommended alcohol-based formulations demonstrated a strong virucidal effect against emerging pathogens, including ZIKV, EBOV, SARS-CoV, and MERS-CoV [73]. Another study conducted in Germany found that the ethanol in the concentration of 42.6% (w/w) was able to destroy SARS coronavirus and MERS coronavirus within 30 s [74].…”
Section: Efficacy Of Alcohol-based Hand Sanitizer Against the Coronavmentioning
confidence: 99%